GAMBARAN TINGKAT KEBUTUHAN PERAWATAN ORTODONTI DI SMPN 2 TAKISUNG BERDASARKAN INDEX OF ORTHODONTIC TREATMENT NEED (Penelitian Dilakukan di Provinsi Kalimantan Selatan Kabupaten Tanah Laut Kecamatan Takisung Desa Tabanio) - Rezalinoor, Muhammad Akbar; Dwi Kurniawan, Fajar Kusuma; Wibowo, Diana (Dentino, 2017)
Background: The incidence of malocclusion in Indonesian is quite high, reaching 80% by the population and it was ranked third after dental caries and periodontal disease. Malocclusion is the deviation of teeth, where the teeth are not in the normal position of the arch. Purpose: The aim of this study is to know the description of level treatment of orthodontic needs students in Junior High School 2 Takisung base on Index of Orthodontic Treatment Need (IOTN). IOTN consisted of two parts which are Aesthetic Component (AC) and Dental Health Component (DHC). Methods: This is a descriptive study, has done in SMPN 1 Takisung at Tabanio village on May - August 2016. The sample of the research is 60 students from the 154 total students. These sample observed using AC and DHC according to IOTN. Results: The result of the study showed that according to AC 65,0% donât need treatment or need minor treatment, 20,0% need a borderline treatment and 15,0% really need treatment. According to DHC 25,0% donât need treatment or need minor treatment, 11,7% need a borderline treatment and 63,3% really need treatment. Conclusion: Based on the results of this study it can be concluded that in the assessment of teeth from the AC angle looks good, but in terms of DHC angle cannot be said to be good which AC and DHC factor it cannot be separated to determined the treatment orthodontic need.